การพัฒนาอุปกรณ์ติดตามระดับแอมโมเนียในน้ำ - อติวิชญ์ สันติกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
The fishing industry today has tended to grow throughout the world and its products also have considerably been in demand. However, the product loss in this industry has still occurred continuously owing to the toxicity of ammonia in water. Therefore, development of the device for monitoring ammonia levels in the fishing industry is necessary. In this research, optical fiber based device was developed. The optical fiber was uncladded and coated with oxazine 170 perchlorate, a fluorescence dye, the color of which could be affected by the change of pH that corresponds to the ammonia level. The color change of the dye would be observed by an optical fiber spectrometer. In this research, preparation of optical fibers for sensing color was studied and tested. The plastic optical fibers were used. First, uncladding of the fiber was investigated. Using acetone and distilled water at the ratio of 1:1 was the most suitable condition for uncladding. Then, the uncladded fiber was tested for color sensing using water, food dye and fluorescence dye. The transmitted light and corresponding absorbed wavelength could be observed. The optical fiber was successfully prepared and possibly be using as a light sensing probe that can be further modified with oxazine 170 and applied for monitoring of ammonia level in water.